Saving American manufacturing : the fight for jobs, opportunity, and national security - Killingsworth, William R. (2014 digital library., 2014)
Documents the decline of economic and intellectual wealth caused by the loss of U.S. manufacturing. Presents clear arguments as to why manufacturing is essential to the United States, and how our nation can capture, benefit, and drive the future of the world economy via embracing global concepts of manufacturing and taking the lead on innovating its future.